The handbook of applied communication research. - O'Hair, Dan; O'Hair, Mary John (Handbooks in communication and media., 2020)
The field of Applied Communication Research (ACR) has made substantial progress over the past five decades in studying communication problems, and in making contributions to help solve them. Changes in society, human relationships, climate and the environment, and digital media have presented myriad contexts in which to apply communication theory. The Handbook of Applied Communication Research addresses a wide array of contemporary communication issues, their research implications in various contexts, and the challenges and opportunities for using communication to manage problems. This innovative work brings together the diverse perspectives of a team of notable international scholars from across disciplines. The Handbook of Applied Communication Research includes discussion and analysis spread across two comprehensive volumes. Volume one introduces ACR, explores what is possible in the field, and examines theoretical perspectives, organizational communication, risk and crisis communication, and media, data, design, and technology. The second volume focuses on real-world communication topics such as health and education communication, legal, ethical, and policy issues, and volunteerism, social justice, and communication activism. Each chapter addresses a specific issue or concern, and discusses the choices faced by participants in the communication process.